Type VI choledochal cyst: a rare entity case report and review of literature - Sharma, Digvijoy; Bheerappa, Nagari; Thumma, Venu Madhav; G., Suryaram Varma; Navakishore, Kunduru (International Surgery Journal, 2017)
Choledochal cysts (CDC) are cystic dilatations of the biliary system, which are usually found in children and uncommon in adults, and type VI choledochal cyst which is isolated cystic dilatation of the cystic duct is a very rare occurrence and only single case reports are documented in the literature. We have reported a case of a young girl who was diagnosed as having Type VI CDC on pre-operative MRCP and found to have the same intraoperatively. She was treated with a simple cholecystectomy with cyst excision.